Development of DPB6043 E-Notes Business Project Mobile Applications - Habsah Mohamad Sabli; Siti Khadijah Sebli Joney; Mohamad Shafiq Mohamed Nasaruddin (International ABEC, 2021)
The Covid-19 pandemic and Movement Control Order (MCO) resulted in the closure of all higher education institutions throughout the country to prevent the spread of this contagious outbreak. The teaching and learning process becomes fully online learning due to this situation. Students living in rural areas face the problem of no internet access. Hence, the purpose of the innovation DPB6043 E-Notes in the form of mobile application to assist students who faced problem with online learning during Covid-19 pandemic. This mobile application was developed using Thunkable and Google Sites based on TAM theory, CBAAM, and ADDIE model. Data were obtained using the survey research method. A total of 33 students from the final semester of Diploma in Business Studies (DPM) program from the Commerce Department, Politeknik Mukah Sarawak participated in the survey. The survey findings further revealed that DPB6043 E-Notes improves students' understanding and is very important for online learning with the highest mean = 4.484. The outcome of this research can benefit the decision-makers of higher institutions in Mukah Sarawak regard to the way to enhance m-learning and promote effective teaching and learning activities as well as strengthening the quality of learning delivery.